2022
DOI: 10.1371/journal.pone.0275591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise and/or educational interventions on physical activity and pain in patients with hip/knee osteoarthritis: A systematic review with meta-analysis

Abstract: Objective To investigate the effectiveness of exercise and/or educational intervention on physical activity and pain in patients with hip/knee osteoarthritis (OA) using systematic review and meta-analysis. Methods We searched randomized controlled trials that investigated physical activity and pain and compared exercise and/or educational intervention with usual care in patients with hip/knee OA in MEDLINE (PubMed), ProQuest, Scopus, and the Physiotherapy Evidence Database (PEDro), including all those publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…37 In addition, the information about health consequences behavioural change technique should be combined with a physical activity intervention. 38 Feedback was mainly obtained from the results of the performance-based tests of function, which resemble daily activities and are easy to understand, and probably motivated the patients to continue with their chosen activities. 26,29 Feedback was in a meta-analysis reported to be the most important behaviour change technique for maintaining long-term physical activity (≥12 months) in adults.…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, the information about health consequences behavioural change technique should be combined with a physical activity intervention. 38 Feedback was mainly obtained from the results of the performance-based tests of function, which resemble daily activities and are easy to understand, and probably motivated the patients to continue with their chosen activities. 26,29 Feedback was in a meta-analysis reported to be the most important behaviour change technique for maintaining long-term physical activity (≥12 months) in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Sasaki et al 37 ) suggested that a combination of education and exercise leads to improved physical activity and pain reduction in hip/knee osteoarthritis patients. Education for patients diagnosed with osteoarthritis includes offering accurate verbal and written information to all people with osteoarthritis to enhance understanding of the condition and its management and to counter misconceptions, such as that it inevitably progresses and cannot be treated.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were anesthetized with 3% sodium pentobarbitone (40 mg/kg) via an intraperitoneal injection (i.p.). After routine shaving and disinfection in the right knee, 10 µl of sterile saline with 1 mg of monosodium iodoacetate (MIA; Sigma-Aldrich; Merck KGaA) was intra-articularly injected (23). Rats in the negative control group received the same volume of vehicle.…”
Section: Methodsmentioning
confidence: 99%